Reborn: Passionate Harmony of the Social Explosion [Renace: Armonía Pasional del Estallido Social] - Bulo-Vargas, V (Universidad De Valparaíso, Chile, 2021)
The current text seeks to complement the concept of social outbreak referring to the political events of October 2019 in Chile with an idea of harmonization and utopian updating in affective-political terms. To do this, in the first place it will be established that it is possible to make a political-affective reading of the social outbreak, taking a detour through what would be the function of the affects in their political dimension, as articulators of communities, to later specify the affective political sense in the context of our social outbreak. Secondly, it will be affirmed that, without denying the very idea of an explosion, at least in part there is also a decantation of a process of utopian harmonization and updating. To deploy these two statements, we will rely mainly on a 19th century author, Charles Fourier, who builds a materialist-affective theory that can provide important insights into our contingency. We will also carry out a reading of the RENACE intervention by Delight Lab to illustrate our thesis. © 2020 Instituto de Filosofía, Universidad de Valparaíso.